A parallel algorithm for chimera grid with implicit hole cutting method. (March 2020) - Hu, Xiaodong; Lu, Zhonghua; Zhang, Jian; Liu, Xiazhen; Yuan, Wu; Liang, Shan; Zhang, Haikuo
The chimera grid methods have been widely used in the simulation of flow over complex configurations and unsteady moving boundary process. Lee and Baeder presented the implicit hole cutting (IHC) method, which improves the practicability and robustness of chimera grid method. But the excessive time consumption of this method restricts the scalability of parallelism. In this article, based on the parallel implementation of IHC method with structured multi-block grid, the factors which restrict the performance and efficiency are analyzed. Cartesian auxiliary grid is introduced to reduce the communication and computing cost. Finally, test cases are presented to demonstrate the effectiveness of this algorithm, and the calculation and data communication are reduced on the premise of maintaining accuracy.